Voting vs. non-voting in Senegal: A nested multinomial logit model approach - Christian H. C. A. Henning; Daniel Diaz; Svetlana Petri (Kiel University, Department of Agricultural Economics, Chair of Agricultural Policy, 2020)
In democratic systems, elections are considered a mechanism to ensure that efficient policies seeking the wellbeing of the population are implemented by the government, although the reality often reflects the opposite. Governments usually act inefficiently due to problems of government performance such as capture and low accountability. In the African continent, the republic of Senegal is considered an example of a stable democracy. Electoral processes in the country have been considered relatively fair. However, the decline in the voter turnout over the past elections suggests that the party system is failing to engage voters. This study assesses influencing factors both in voting behavior in Senegal and in the decision to abstain. We estimated nested multinomial logit models including the alternative Abstention to determine the importance of the non-voters group in the policy making process. We found that even though people in general make their decision more non-policy oriented, abstainers, compared to those who cast a vote, tend to choose more retrospectively oriented and less policy and nonpolicy oriented. Furthermore, our findings show that this group of non-voters hold the government more accountable and have a higher political weight for the incumbent party. Thus, they could incentive the government to choose and implement more efficient policies. [...]
Keywords: Q18; C31; C35; C38; 330; probabilistic voter model; capture; accountability; agricultural policy; Senegal; Africa